Analysis Of The Differences And Relevance Of Islamic And Conventional Banking Principles - Antonius Prahendratno (CV. Syntax Corporation Indonesia, 2023)
The purpose of writing this article is to have a better understanding of the differences between Islamic and conventional banking as well as the relevance of Islamic banking principles in the current global economic context. The research method used is qualitative method, this study is descriptive analytic, this is to describe and analyze the system of Islamic financial institutions with the system of conventional financial institutions. Results: Sharia banks serve as a means to accumulate public savings and develop them. The point is that Sharia Bank is an institution that functions to invest public funds in accordance with Islamic recommendations effectively, productively and for the benefit of Muslims. The main objective of Sharia Bank, which is to unite Muslims, restore the strength, role, and position of Islam on this earth can be achieved. Conventional Banks are established to obtain maximum material benefits, while Islamic Banks are established to provide material and spiritual welfare. This material and spiritual welfare is obtained through halal funds collection and distribution. This means that Sharia Bank will not distribute funds to liquor factories or other businesses that cannot be guaranteed that the results come from halal activities. Therefore, it can be said that the concept of profit in conventional banks is more inclined, focusing on the angle of material profits, while the concept of profit in Islamic banks must pay attention to profits from the worldly and ukhrawi (hereafter) angles.